2003
DOI: 10.3102/00346543073001089
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Characteristics and Student Achievement Gains: A Review

Abstract: A large body of studies exists that examines the relationship between student achievement gains and the characteristics of teachers. To help policymakers and researchers use and build on this body of studies, this article reviews the studies systematically and synthesizes their results with deliberate consideration of each study’s qualities. Determinate relationships are described for four categories of teacher characteristics: college ratings, test scores, degrees and coursework, and certification status. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
634
0
30

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(720 citation statements)
references
References 34 publications
21
634
0
30
Order By: Relevance
“…A cross-sectional analysis of the 2003 Trends in International Mathematics and Science Study data across 46 countries showed that countries with better quality teachers produced higher mathematics achievement compared to those with poor quality teachers (Akiba et al, 2007). Numerous studies on teacher quality (Darling-Hammond and Youngs, 2002;Rice, 2003;Wayne and Youngs, 2003) have been reported and most of these studies focused on teacher certification, subject-matter knowledge, pedagogical knowledge and teaching experience, since these qualities of teachers are associated with high student achievement. Recognizing the importance of teacher quality, Cohen-Vogel (2005) noted that teachers' improvement has been the major focus of educational reforms in the past 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional analysis of the 2003 Trends in International Mathematics and Science Study data across 46 countries showed that countries with better quality teachers produced higher mathematics achievement compared to those with poor quality teachers (Akiba et al, 2007). Numerous studies on teacher quality (Darling-Hammond and Youngs, 2002;Rice, 2003;Wayne and Youngs, 2003) have been reported and most of these studies focused on teacher certification, subject-matter knowledge, pedagogical knowledge and teaching experience, since these qualities of teachers are associated with high student achievement. Recognizing the importance of teacher quality, Cohen-Vogel (2005) noted that teachers' improvement has been the major focus of educational reforms in the past 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…Wayne and Youngs (2003) examined the characteristics of effective teachers that are interrelated to student effectiveness. Cruickshank, Jenkins and Metcalf (2003) believe that caring, supportive, knowledgeable teachers can effectively help students to learn.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Traditionally, the level of education and years of teaching have been used as main indicators of teachers' knowledge and competence (Wayne & Youngs, 2003). Studies have found that high school students who were taught by a teacher with a degree in mathematics outperformed their counterparts taught by a teacher without a mathematics degree (Goldhaber & Brewer, 2000;Wayne & Youngs, 2003).…”
Section: Factors Influencing Teachers' Knowledgementioning
confidence: 99%
“…Studies have found that high school students who were taught by a teacher with a degree in mathematics outperformed their counterparts taught by a teacher without a mathematics degree (Goldhaber & Brewer, 2000;Wayne & Youngs, 2003). The number of courses in mathematics and mathematics education the teachers took had a positive correlation to their students' achievement in mathematics at the secondary school level (Monk & King, 1994).…”
Section: Factors Influencing Teachers' Knowledgementioning
confidence: 99%